PENGARUH KINERJA KEUANGAN, RISK BASED CAPITAL, UKURAN PERUSAHAAN,GOOD CORPORATE GOVERNANCE,DAN MAKRO EKONOMI TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN ASURANSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Anggraini, Ponisa; Yuniarti , Nensi; Ranidiah , Furqonti; Astuti, Budi (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the influence of financial performance, risk-based capital, company size, good corporate governance, inflation, and exchange rates on financial distress in insurance companies listed on the Indonesia Stock Exchange for the period 2019-2023. The research method used is a quantitative method with multiple linear regression analysis using secondary data processed with SPSS 30. The results show that financial performance and exchange rates have a significant effect on financial distress, while risk-based capital, company size, good corporate governance, and inflation do not have a significant effect. The conclusion of this study states that only financial performance and exchange rates have a significant effect on financial distress in insurance companies listed on the Indonesia Stock Exchange during the study period. Keywords: Keywords: Financial Distress, Financial Performance, Exchange Rate, Risk Based Capital, Insurance Companies